Pengaruh Kepuasan Pengguna Aplikasi Belanja Online Berbasis Mobile Menggunakan Metode EUCS - Indah Kurniasih; Desi Pibriana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The internet is one medium that can be used as a marketing medium for a business. The internet has never been spared from technological developments which at present have experienced a very rapid increase, one of which is technological developments in the field of commerce. In the world of commerce there is the term e-commerce or electronic commerce. The user basically will do an assessment in every transaction he does, both conventional transactions and digital transactions. The better the service provided by the service provider, the more likely the user to return to using the service means that the user is satisfied using the application. This study discusses the satisfaction of users of online shopping applications PT. ABC International Indonesia. Analysis of user satisfaction is measured using the End user computing satisfaction (EUCS) method which consists of 5 factors, namely: content, accuracy, format, ease of use, and timeliness. Data collection was carried out through a questionnaire filled out by users of PT. ABC International Indonesia. To process the data obtained from the results of the questionnaire using SPSS software. From the analysis conducted, it shows that the content, accuracy, format, ease of use and timeliness variables proposed by all hypotheses are accepted. While based on the F test shows the content, accuracy, format, ease of use and timeliness variables simultaneously affect the satisfaction of users of online shopping applications.